Hydraulic Simulation of Erosion and Scour at Cunas Bridge, Huamancaca Chico District, Chupaca-Peru - Enriquez, Evelyn Julissa de la Pena; Campomanes, Giovene Perez (Engineering, Technology & Applied Science Research, 2026)
This study developed a hydraulic simulation to identify critical erosion zones and to propose appropriate structural protection measures. Topographic, hydrological, and sedimentological data were processed to model both historical flow conditions and climate change scenarios using QGIS, HEC-HMS, and HEC-RAS. The results indicate that, under historical conditions, maximum erosion depths reached 5.54 m, while under climate change scenarios, they increased to 7.78 m. An eroded river reach of 70.38 m was identified, with an average erosion impact of 1.81 m along the bridge, indicating a high level of structural risk, which is further exacerbated by sediment and debris accumulation in the riverbed. The analysis shows that erosion of the Cunas River has caused significant deterioration of bridge piers and abutments, adversely affecting local connectivity and the regional economy. For future bridge designs, it is proposed that maximum discharge be considered together with sediment transport effects and projected climate change. In addition, structural riverbank protection measures, such as riprap, gabions, groynes, dikes, retaining walls, or channelization works, should be incorporated into design and mitigation strategies.